1997
DOI: 10.1128/jcm.35.12.3269-3273.1997
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Vitek GNI+ and Becton Dickinson Microbiology Systems Crystal E/NF identification systems for identification of members of the family Enterobacteriaceae and other gram-negative, glucose-fermenting and non-glucose-fermenting bacilli

Abstract: We evaluated the Vitek GNI؉ and Becton Dickinson Crystal E/NF identification systems for their ability to accurately identify 619 and 626 strains, respectively, of members of the family Enterobacteriaceae and other glucose-fermenting and non-glucose-fermenting gram-negative rods. All strains tested were taken from a stock collection and passed three times on 5% sheep blood agar prior to testing. These strains represented a more rigorous challenge to both systems than one resulting from the testing of consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 7 publications
2
23
1
Order By: Relevance
“…When analyzed with respect to the organisms tested, the highest essential agreements were observed with isolates of the family Enterobacteriaceae (96.6%) and gram-positive organisms (95.6%). As other investigators have noted with other systems (22,23), lower essential agreement was observed with NFGNRs (88.0%). Nevertheless, in contrast to automated instrument systems with short incubation times (14,15), susceptibility testing results could be obtained for all organisms considered to be slowly growing organisms.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…When analyzed with respect to the organisms tested, the highest essential agreements were observed with isolates of the family Enterobacteriaceae (96.6%) and gram-positive organisms (95.6%). As other investigators have noted with other systems (22,23), lower essential agreement was observed with NFGNRs (88.0%). Nevertheless, in contrast to automated instrument systems with short incubation times (14,15), susceptibility testing results could be obtained for all organisms considered to be slowly growing organisms.…”
Section: Discussionsupporting
confidence: 70%
“…arizonae ATCC 12323 strain. As with other systems, less accuracy (92.0%) than that observed with isolates of the family Enterobacteriaceae was shown when only NFGNRs were taken into account (8,22,24,25,27). In all cases, the API system was used as the "gold standard" for bacterial identification, as it is a well-recognized system for this purpose (25,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are similar to those reported by Colosante et al (3) in their comparison of GNI and GNIϩ cards. In another study which included an evaluation of the GNIϩ card, O'Hara et al reported an accuracy of 87.6% for the GNIϩ cards; however, the authors acknowledged that the isolates included in their study represented a vigorous challenge to the products evaluated (6). The results of our study for the GNI card are very similar to results reported by Robinson et al (8) and Rhoads et al (7) for the GNI card.…”
supporting
confidence: 85%
“…Commercial methods. With the ever-increasing cost of commercial identification methods (73,74), spot testing is both rapid and cost-effective (64) and can be helpful in many instances. If the colonies on a sheep blood agar plate swarm and are oxidase negative and if a spot indole test using para-dimethylaminocinnemaldehyde reagent is negative, the probability of the culture being either P. mirabilis or P. penneri is very high.…”
Section: Phenotypic Identification Of the Speciesmentioning
confidence: 99%